APPROACH OF HINDUISM TO ITS SCRIPTURES - Nayak, G C (Journal of Dharma, 1996)
The Vedas occupy a unique position in Hinduism. Even the distinction between a believer and a non-believer is made in Hinduism, not on the ground of belief or dis-belief in God but on the ground of belief or disbelief in the authority of the Vedas. Six orthodox systems of philosophy, or ästika daršanas of Hinduism, as they are called, are regarded as orthodox or ästika simply because all these systems of philosophy believe in the authority of the Vedas. Some of these systems are regarded as ästika (orthodox) only on this ground even if they do not believe in the existence of God, e.g. Mimälñsä and Sämkhya philosophies, which do not believe in the existence of God, are regarded as ästika daršanas simply because they believe in the authority of the Vedas. Similarly Buddhism, Jainism, and Cãrväka are regarded as heterodox or nästika daršanas, not on the ground that they do not believe in the existence of God but on the ground that they do not believe in the authority of the Vedas. In recent times, during the 19th Century, the Vedic authority has also been questioned by some thinkers of Hindu Renaissance movement like Debendranath Tagore and Keshab Chandra Sen, while others like Swami Dayananda Saraswati have, on the other hand, been fàmous for their championing the theory of Vedic infallibility and advocating religious and social reforms on the basis of an appeal to the Vedic authority